The Design Of Customer Knowledge Reporting System Intervention To Improve The Performance Of Medical Representative At Pt. X Buf - Rusvita, Lidia; Mansoer , Wilman D. (International Journal of Science, Technology & Management, 2023)
The change in government policy of product listing cycle of two years created the power of buyers/customers to make decisions to buy products based on price competitiveness. PT. X BUF products is premium and facing the treats on price. However, opportunities lie in its excellent quality and benefit. It is imperative to transfer product knowledge to the customer and gain customer’s knowledge and experience on product. The flow of knowledge to the to the customer on product is crucial to influence the customer in decision making using the product. The knowledge and experience from customers on a product are crucial to the organization on understanding product adoption. This knowledge sharing takes place with the right message to the right customer generate Demand. This research is aimed at designing an intervention on customer knowledge reporting system to improve the work performance of Medical Representative, frontline sales person, at PT. X BUF. The research applied quantitative methodology by collecting data from a set of questionnaires. The finding of the study shows that work process as well as manager role and function have significant impact on willingness of Medical Representative in sharing their customer’s knowledge which eventually impact their work performance in particular and company performance in general.